2013
DOI: 10.1021/jz301859k
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts Transform While Molecules React: An Atomic-Scale View

Abstract: We explore how the atomic-scale structural and chemical properties of an oxide-supported monolayer (ML) catalyst are related to catalytic behavior. This case study is for vanadium oxide deposited on a rutile α-TiO2(110) single-crystal surface by atomic layer deposition (ALD) undergoing a redox reaction cycle in the oxidative dehydrogenation (ODH) of cyclohexane. For measurements that require a greater effective surface area, we include a comparative set of ALD-processed rutile powder samples. In situ single-cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 48 publications
1
19
1
Order By: Relevance
“…[33][34][35][36] Recently we have demonstrated that XSW is a unique in situ tool to understand the atomic-scale behavior of oxide-supported planar model catalysts during various chemical reactions. 12,[15][16][17][37][38][39][40] In this work, we use XSW to observe chemical state-dependent changes in the V and W geometry and surface site occupancy. We also determine the fraction of atoms that are uncorrelated to the substrate lattice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36] Recently we have demonstrated that XSW is a unique in situ tool to understand the atomic-scale behavior of oxide-supported planar model catalysts during various chemical reactions. 12,[15][16][17][37][38][39][40] In this work, we use XSW to observe chemical state-dependent changes in the V and W geometry and surface site occupancy. We also determine the fraction of atoms that are uncorrelated to the substrate lattice.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that monolayer (ML) and sub-ML vanadia supported on TiO 2 and other oxides can go through both structural and chemical state changes during reduction-oxidation (redox) reaction cycles. 2,10,37,38,41,42 In contrast, ML and sub-ML tungsten oxide lms supported on oxide substrates tend to be immobile and irreducible from the W 6+ state under similar catalytic conditions. 12,43-45 A notable exception is for sub-ML tungsten oxide on the reducible substrate a-Fe 2 O 3 (0001), for which a reduction to W 5+ and corresponding redox-reversible structural shis are observed.…”
Section: Introductionmentioning
confidence: 99%
“…In Figure 5a, the black curve (labeled 'N2, 300 °C') corresponds to the catalyst in a nitrogen flow at 300 °C before exposure to the reaction gas mixture. Features located at around 919 and 1036 cm −1 and at around 1849 and 2002 cm −1 have previously been assigned to V-O-V and V=O stretching modes of surface VOx species and their first overtones, respectively [2,50,89,90]. The feature at 1203 cm −1 has been ascribed to L acid sites on TiO2 [91].…”
Section: Operando Characterization Of Tio 2 /Sba-15+3xvo Xmentioning
confidence: 88%
“…The use of in situ electron paramagnetic resonance (EPR) and X-ray absorption spectroscopy (XAS) under reaction conditions has revealed the reducing/reoxidizing processes to be accompanied by changes of the vanadium valence and VO x surface structure [45][46][47][48]. Feng et al reported VO x with polymeric structure to be redox-active and provided an atomic view of the change of the VO x structure with redox state [49][50][51]. Consistently, density functional theory (DFT) results showed that formation of both oxidized and reduced VO x , i.e., V 5+ and V 4+ , kept the vanadyl bond intact for isolated VO x on TiO 2 , as verified by in situ EPR data for VO x /TiO 2 exposed to ammonia [52].…”
Section: Introductionmentioning
confidence: 99%
“…Metal/metal oxide catalysts are commonly used catalysts for ODH of cyclohexane [1d,6c,e,8] . However, deep oxidation and dehydrogenation [9] often occur inevitably yielding undesired CO x and benzene as byproducts.…”
Section: Introductionmentioning
confidence: 99%